2013
DOI: 10.3389/fncel.2013.00149
|View full text |Cite
|
Sign up to set email alerts
|

Seizure-like activity in hyaluronidase-treated dissociated hippocampal cultures

Abstract: The extracellular matrix (ECM) plays an important role in use-dependent synaptic plasticity. Hyaluronic acid (HA) is the backbone of the neural ECM, which has been shown to modulate α-amino-3-hydroxyl-5-methyl-4-isoxazolepropionate (AMPA) receptor mobility, paired-pulse depression, L-type voltage-dependent Ca2+ channel (L-VDCC) activity, long-term potentiation and contextual fear conditioning. To investigate the role of HA in the development of spontaneous neuronal network activity, we used microelectrode arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 27 publications
2
83
2
1
Order By: Relevance
“…Interestingly, heparin binds L-VDCC [21]; moreover, another polyanionic glycan, hyaluronic acid, supports activity of L-VDCCs [22] and its enzymatic removal leads to appearance of epileptiform activity similar to that reported in this study [23]. Thus, modulation of L-VDCC activity can be one of the mechanisms by which a deficit of HSs induces HSP.…”
Section: Discussionmentioning
confidence: 51%
“…Interestingly, heparin binds L-VDCC [21]; moreover, another polyanionic glycan, hyaluronic acid, supports activity of L-VDCCs [22] and its enzymatic removal leads to appearance of epileptiform activity similar to that reported in this study [23]. Thus, modulation of L-VDCC activity can be one of the mechanisms by which a deficit of HSs induces HSP.…”
Section: Discussionmentioning
confidence: 51%
“…This study demonstrated that application of hyaluronic acid to transfected CHO cells potentiated L-VDCC-mediated currents, while enzymatic digestion of hyaluronic acid with hyaluronidase impaired L-VDCC-mediated currents, Ca 2+ transients in dendritic spines, LTP and contextual fear conditioning (Kochlamazashvili et al, 2010). Hyaluronidase treatment led to appearance of long-lasting Ca 2+ transients and epileptiform bursts of neuronal activity in cultured hippocampal neurons grown on microelectrode arrays (Vedunova et al, 2013). …”
Section: Introductionmentioning
confidence: 94%
“…Dissociated hippocampal cells were taken from C57BL/6 mice embryos (E18) and cultured on coverslips during 14 days in vitro (DIV) according to the previously developed protocol [9]. The cell viability was maintained under constant conditions of 35.5 ∘ C, 5% CO 2 and a humidified atmosphere in a cell culture incubator.…”
Section: Cell Culturementioning
confidence: 99%